Person-centred care for dementia patients (PEAR) back-end and front-end systems development - Rizwan Nusrath Fathima (Nanyang Technological University, 2024)
Dementia is an irreversible cognitive disorder that interferes with one’s memory, thinking, and behaviour leading to a great deterioration in the quality of life [1]. As dementia has no cure, palliative care is often opted for. One form of which is Person-Centred Care. PEAR is a long-term project and monolithic architecture, proved to be a cause of deterioration to its code base, given that the time each batch of developers spend on it is very little. It takes a significant amount of time for each batch of developers to understand the codebase, and poor coding practices had led to spaghetti code and a tightly coupled system that was highly unstable. Furthermore, as the project spanned years, the issue of the technology stack becoming outdated and thus going out of support could happen again, hence microservices architecture was opted for. The PEAR system is a closed loop application that facilitates person centred care in a healthcare centre. However, due to compatibility issues with hosting a .NET application on a Linux server, a significant portion of PEAR had to undergo a revamp. This revamp entailed a software system architecture redesign, database redesign, data migration and development. The author focused on contributing a design solution for PEAR, including the database redesign as well as working on Data Migration. As part of this design solution, PEAR migrated from a monolithic architecture to a microservices architecture.